A new species of Anastrepha from Colombia related to Mexican fruit fly (Diptera: Tephritidae) - Norrbom, A.L.=700 1 Korytkowski, Ch.A.; Gonzalez, F.; Orduz, B.
(Es, En)
Ilus., 7 ref.
Keywords: ANASTREPHA; TEPHRITIDAE; INSECTA; TAXONOMIA; ESPECIES NUEVAS; REGISTRO; COLOMBIA; MOSCA DE LA FRUTA